Akutansi Dan Manajemen Keuangan Pada Organisasi Berbasis Islam: Studi Kasus Pada Beberapa Pondok Pesantren Di Kabupaten Lombok Utara - NTB - Saipul Arni Muhsyaf; R. Sapto Hendri BS; Iman Waskito (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2021)
Religion-based organizations are expected to be the best examples of organizations that are rich in core values ​​such as integrity, professionalism, partnership and stewardship. Unfortunately, religious-based organizations such as pondok pesantren are more focused on social service issues so they do not have a control mechanism to protect the pesantren's resources and continuously provide information to their stakeholders regarding the organization's financial status and fundraising efforts. This study aims to assess the practice of financial management in Islamic boarding schools (pondok pesantren) in North Lombok Regency. The research results reveal, among others (1) the financial reports used by the boarding school unit are only limited to cash books, (2) the boarding school is challenged to provide/prepare proficient accounting personnel in the boarding school financial management work unit, (3) It is important for the leadership to manage the resources of this boarding schools, (4) periodic comparisons between planned and actual budgeting are in a weak position in Islamic boarding schools, (5) Some Islamic boarding schools have strong experience and others still need development, (6) although the majority of Islamic boarding schools conduct external audits, there are several Islamic boarding schools that have not accommodated the audit mechanism.